Intra-blood-brain barrier synthesis of human immunodeficiency virus antigen and antibody in humans and chimpanzees. - Goudsmit, J (1987)
The presence of human immunodeficiency virus (HIV) antigens in cerebrospinal fluid (CSF) was associated with progressive encephalopathy in adult and pediatric patients with acquired immunodeficiency syndrome (AIDS). HIV antigen was detected in CSF from 6 of 7 AIDS patients with progressive encephalopathy. By contrast, HIV antigen, whether free or complexed, was detected in CSF from only 1 of 18 HIV antibody seropositive patients without progressive encephalopathy and from 0 of 8 experimentally infected chimpanzees without clinical signs. Intra-blood-brain barrier synthesis of HIV-specific antibody was demonstrated in the majority of patients with AIDS (9/12) or at risk for AIDS (8/13) as well as in the experimentally infected chimpanzees, indicating HIV-specific B-cell reactivity in the brain without apparent neurological signs. In 6 of 11 patients with HIV infection, antibodies synthesized in the central nervous system were directed against HIV envelope proteins. Active viral expression appears to be necessary for both the immunodeficiency and progressive encephalopathy associated with HIV infection.